2014
DOI: 10.1007/s00520-014-2215-2
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of taste and smell alterations reported by patients after starting treatment for lung cancer

Abstract: Purpose Taste and smell alterations (TSAs) in patients with lung cancer are poorly understood. This study investigates characteristics of TSAs when most severe, reported by patients after starting treatment for lung cancer. Methods Data was collected regarding TSAs, symptoms, food intake and nutritional status through structured interviews using the Taste and Smell Survey, the Patient-Generated Subjective Global Assessment and 3-day food diaries. This data derives from a longitudinal project and the interview … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
8

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 32 publications
(41 reference statements)
2
30
0
8
Order By: Relevance
“…Also, previous studies performed in cancer patients found that taste changes were more prevalent in women compared to men (7,11,16), whereas other studies found no gender differences (3,22). A study in 89 lung cancer patients showed that women reported more often stronger sensations, while men reported weaker sensations more frequently (24). Reasons for gender differences regarding taste changes are currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Also, previous studies performed in cancer patients found that taste changes were more prevalent in women compared to men (7,11,16), whereas other studies found no gender differences (3,22). A study in 89 lung cancer patients showed that women reported more often stronger sensations, while men reported weaker sensations more frequently (24). Reasons for gender differences regarding taste changes are currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…7 The survey has since been widely used to assess taste and smell alterations in patients with lung cancer, head and neck cancer, and advanced cancer. 6,8,9 Taste was evaluated by 9 items which asked patients to indicate any self-perceived changes in their sense of taste or tastes of particular foods, to assess whether they have noticed any changes (stronger or weaker) in the 4 main tastes (sweet, salty, bitter, and sour), and to rate the severity of changes. The 8 items were scored from 0-1 points and 1 item was scored 1-2 points, resulting in an overall possible taste score from 1-10 points.…”
Section: Taste and Smell Surveymentioning
confidence: 99%
“…However, high intakes of salt probably increase the risk of nasopharyngeal and stomach cancer (22,48). Gender differentiation was not found statistically significant for salt, sweet, sour, or spicy food consumption, unlike another study where most of the female participans did not prefer salty (49).…”
Section: Discussionmentioning
confidence: 56%